Clinico-demoghraphic profile and outcome of critically ill poisoning patient admitted in the ICU of the largest tertiary care government hospital in Dhaka, Bangladesh - Sarker, Subroto Kumar; Salim, Mohammad; Ahmed, Alisa; Mahjaben, Mousume; Tumpa, Benozir Sofi (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: Acute poisoning is a common chief complaint leading to emergency department visits andhospital admissions in developing countries such as Bangladesh. Aim: To study the demographic and clinical profiles of patients admitted to the ICU with acute poisoningand to study the factors that predict their mortality. Methodology: This observational study recruited all eligible 74 poisoning patients admitted in theintensive care unit from 1st July 2019 to 30th June 2020. This study is conducted in the Intensive CareUnit of Dhaka Medical College Hospital, Dhaka, Bangladesh. Result: Total 74 poisoning patients were admitted in the intensive care unit, of them female (55.54%)was more than male(44.59% ). Among the patients 67( 90.54 %) patient were Muslims and 43(58.10%)were married. The highest incidence of poisoning 28 (37.83%) were observed in the age group 11 to 20year and the mean age was 23.74 years. The majority of poisoning cases was suicidal intension(87.83%),accidental was 6.75% and homicidal or street poisoning was 5.40%.The most common type of poisoningwas organophosphorus compound (52.70%) followed by Drug overdose (16.21%), Paraquat poisoning(9.45%), rat killer( 5.4%),Insecticide poisoning (4.05%),Corrosive poisoning (2.74%).The most commonroute of poisoning was ingetion. Mechanical ventilation required 52.70% patients, majority of patientsrequired shorter period (1 to 5 days) of mechanical ventilation and mean duration of mechanical ventilationis 6.33 days . 83% patient were shifted /dischared from the ICU within 1 to 5 days. Mean duration was8.13 day in case of mechanical ventilated patients, but in non-ventilated patients, ICU stay was much lessthan ventilated patients. In this study, the mortality rate was 31% . Conclusion: Early ICU admission and appropriate management of patients after ingestion of poisonousagent results in reduced morbidity and mortality. JBSA 2020; 33(2): 85-91